Biomedical cell product model for preclinical studies carried out on a large laboratory animal - M. N. Egorikhina; D. Ya. Aleinik; Yu. P. Rubtsova; I. N. Charykova; A. A. Struchcov; A. A. Ezhevskaya; V. I. Zagrekov; L. N. Sosnina; E. V. Zagaynova (Вестник трансплантологии и искусственных органов, 2020)
Objective: to develop a model of a biomedical cell product that is consistent with the «homologous drug» strategy  based on protocols for preparing the cell component and scaffold carrier for preclinical studies on a large laboratory  animal (pig). Materials and methods. Biomedical cell products and skin equivalents (SE), were formed using  plasma cryoprecipitate prepared from blood plasma of healthy donors and mesenchymal stem cells (MSCs) of  human adipose tissue. Cryoprecipitate from pig blood plasma and human adipose tissue-derived MSCs were used   to form model skin equivalents (mSE). Bright-field microscopy, phase-contrast microscopy (Leica DMI 3000B)  and fluorescence microscopy (Cytation 5 imager; BioTek, USA) were used to monitor the state of cells in the  culture and in the composition of the equivalents. Scaffolds for equivalents were tested for cytotoxicity (MTT test,  direct contact method). The cell distribution density was characterized by author’s method (Patent No. 2675376  of the Russian Federation). Results. An mSE was developed for preclinical studies on a large laboratory animal  (pig). In the mSE, components that change from halogen to xenogenic conditions during transplantation to the  animal were replaced. A comprehensive approach to preparing mSE was presented. It includes sampling of primary  pig biomaterial, extraction and characterization of adipose tissue-derived MSCs, preparation of a scaffold  carrier for the corresponding «homologous drug» strategy. Cytotoxicity of the mSE scaffold was evaluated. It  was shown that mSE provides mechanical support (similar to SE) to cells, as well as comparable development of  cellular events during cultivation. Conclusion. A model of a biomedical cell product was developed. This model  is consistent with the «homologous drug» strategy for preclinical studies on a large laboratory animal (pig). The  paper presented a comprehensive approach to developing a model equivalent based on protocols for preparation  and testing of the cellular component, the scaffold carrier and the ready-to-use model equivalent.